For a real number x > 0 , let F ( x ) = ∫ x 2 4 x 2 sin t d t
For a real number t > 0 , let t denote the positive square root of t . If F ′ is the first derivative of F , find the value of F ′ ( 2 π ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We could use leibnitz from the starting, isnt it sir?
Log in to reply
Don't quite know what Leibnitz formula. But I see the reverse of integration.
F ′ ( x ) ⟹ F ′ ( 2 π ) = d x d ∫ x 2 4 x 2 sin t d t = d x d ( ∫ x 2 c sin t d t + ∫ c 4 x 2 sin t d t ) = d x d ( − ∫ c x 2 sin t d t + ∫ c 4 x 2 sin t d t ) = − 2 x ⋅ sin x 2 + 8 x ⋅ sin 4 x 2 = − 2 x sin ∣ x ∣ + 8 x sin ∣ 2 x ∣ = 2 x ( 4 sin ∣ 2 x ∣ − sin ∣ x ∣ ) = − π for some constant c Apply the Fundamental Theorem of Calculus
We have
F ( x ) = ∫ x 2 4 x 2 sin t d t .
Applying Leibniz Rule , we get
F ′ ( x ) = sin ( 2 x ) × 8 x − sin ( x ) × 2 x .
Setting x = 2 π above , gives
F ′ ( 2 π ) = sin ( π ) × 4 π − sin ( 2 π ) × π = − π
Problem Loading...
Note Loading...
Set Loading...
F ( x ) = ∫ x 2 4 x 2 sin t d t = 2 ∫ x 2 x u sin u d u = 2 ( ∫ a 2 x u sin u d u − ∫ a x u sin u d u ) Let u 2 = t ⟹ 2 u d u = d t a > 0 is a constant
⟹ F ′ ( x ) = 2 × d x d ( ∫ a 2 x u sin u d u − ∫ a x u sin u d u ) = 2 ( 2 x sin 2 x − x sin x )
⟹ F ′ ( 2 π ) = − π